ISLAMIC LAW REVIEW OF THE PRACTICE OF RUBBER PLANTATION MUSAQAH IN LUBUK DAGANG VILLAGE SAMBAS DISTRICT - Yulianti, Wirna; Asman, Asman; Rosana, Mayang (Archipelago Journal of Southeast Asia Islamic Studies, 2023)
This research is motivated by the practice of rubber plantation musaqah using a profit sharing system between both parties. This practice is in Lubuk Dagang Village, Sambas District. With the practice of rubber plantation musaqah which is based on the absence of a written agreement in Islamic law, it makes it easier for one of the parties to default on the agreement. This research method uses a type of qualitative research that is field research. Meanwhile, this research uses an empirical approach method, because it is qualitative research with an empirical approach that examines law which is conceptualized as real behavior in society to describe the conditions seen in the field, namely in Lubuk Dagang Village, Sambas District, in the practice of musaqah. To obtain data, researchers used interview and observation guidelines. Based on the research results obtained by researchers, it can be concluded that. 1) the practice of rubber plantation musaqah in Lubuk Dagang Village, Sambas District is carried out on the basis of mutual assistance carried out by both parties with mutual trust without any time limit set by the rubber plantation owner for the cultivator to work on it. Profit sharing that was agreed upon at the beginning of the agreement 4:6 and 3:7. 2) According to the Review of Islamic Law in the practice of rubber plantation musaqah in Lubuk Dagang Village, the time limit that is not determined by the rubber plantation owner is not in accordance with Islamic law and the terms of the musaqah contract.